Pengembangan E-Modul Berorientasi Pemecahan Masalah Untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - I M. Suarsana; G.A. Mahayukti (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2013)
The aim of this research was to develop a problem solving oriented e-module of algebra, to analiyze effectiveness of the use of emodule in improving critical thinking skill, and to describe response of students to the e-module. This research was conducted using the design of research and development by adopting a Plomp model as follows: a) preliminary investigation phase, b) design phase, c) realization/construction phase, d) test, evaluation, and revision phase and, e) implementation phase. The result shows that: 1) emodule has been prepared good quality, but still need to be refined again, 2) critical thinking skill of students can be enhanced to good level, 3) the response of students to the lectures which implemented using the e-module is very positive